Correlation between CRP Level and Neutrophil Extracellular Traps in Malignancy Patients with Neutropenic Fever - Phey Liana; Kemas M. Yakub; Eny Rahmawati; Berliana Agustin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
The mortality and morbidity rate of neutropenic fever is quite high. The source and severity of infection must be evaluated quickly in neutropenic patients. C-Reactive Protein (CRP) and Neutrophil Extracellular Traps (NETs) are known as markers for severeinfection. Besides, NETs also play a role in the development and metastasis of cancer but the mechanism is still unclear. C-reactive protein is a marker that is routinely used for infection. However, the correlation between CRP levels and NETs in malignant patients with neutropenia is unknown. Therefore this study was conducted to determine the correlation between CRP levels and NETs in malignant patients with neutropenia. This research was a cross-sectional observational study. The samples were malignant patients with neutropenia who were treated in the Pediatric Ward of Dr. Mohammad Hoesin Hospital, Palembang and met the inclusion and exclusion criteria. Sampling was done by consecutive sampling. C-reactive protein level and NETs weretested by immunoturbidimetry and ELISA methods. Data were analyzed with the Pearson test (p <0.05). The mean of CRP and NETs level were 170.17±121.52 mg/L and 0.77±0.39 ng/mL, respectively. The correlation test between CRP level and NETs in malignancy patients with neutropenic fever showed r=0.228 and p=0.362. The results showed no significant correlation between CRP level and NETs in malignant patients with neutropenic fever.